School Leadership- from Vision to Practice: Untying the Knots for Integration of EWS Children - Kaushal, Savita (Voices of Teachers and Teacher Educators, 2022)
School leaders, specifically the school head, have a crucial role to play in establishing goals, fostering a healthy school climate that includes the proactive school mindset, and fostering essential staff enthusiasm and dedication that are necessary for success even in difficult situations. This paper is based on the case study of a school where the principal took the bold step of integrating students from Economically Weaker Section (EWS) families into the school. EWS children suffer significant hurdles to integration, education, and learning because of poverty and social marginalisation. Inequality in learning achievement is a problem that is particularly evident in children from economically disadvantaged families, and they are exacerbated by their social and familial disadvantages. They are known as the “children at the bottom of the pyramid” because they are frequently forgotten and are often left behind. Within this context, the author in this paper has described the practices adopted by the school head that aimed at improving learning and equity amongst the most disadvantaged children. The paper points out that a principal’s leadership style can impact the integration of the EWS learners.learning outcomes, and instructional objectives—with examples specifically related to the Indian context. The paper discusses some caveats associated with standards-based education systems and concludes with suggestions for improvement and implementation.